Episodic memory in transient global amnesia: encoding, storage, or retrieval deficit?. Issue 2 (1st February 1999) - Eustache, Francis; Desgranges, Béatrice; Laville, Peggy; Guillery, Bérengère; Lalevée, Catherine; Schaeffer, Stéphane; de la Sayette, Vincent; Iglesias, Serge; Baron, Jean-Claude; Viader, Fausto
Abstract : OBJECTIVES: To assess episodic memory (especially anterograde amnesia) during the acute phase of transient global amnesia to differentiate an encoding, a storage, or a retrieval deficit. METHODS: In three patients, whose amnestic episode fulfilled all current criteria for transient global amnesia, a neuropsychological protocol was administered which included a word learning task derived from the Grober and Buschke's procedure. RESULTS: In one patient, the results suggested an encoding deficit, and in two others, a storage deficit. CONCLUSIONS: The encoding/storage impairment concerning anterograde amnesia documented in our patients stands in clear contrast with the impairment in retrieval which must underly the retrograde amnesia that also characterises transient global amnesia. This dissociation in turn favours the idea of a functional independence among the cognitive mechanisms that subserve episodic memory.